Analysing the English communication needs of service technicians in the pest control industry - Hee, S.C.; Zainal, Azlin Zaiti (Universiti Putra Malaysia, 2018)
This paper analyses the English language needs of service technicians in the pest control industry. The paper aims to provide a detailed understanding of the communication requirements in the workplace in order to develop a language course appropriate for their needs. In the pest control industry, service technicians are known to be the first point of contact with the customers. The nature of their job involves servicing customers’ premises either weekly, bi-weekly or monthly. This calls for interaction with customers, which requires the ability to perform communicative functions to address customer inquiries and handle their requests and complaints. This paper utilises a needs analysis questionnaire for data collection. The questionnaire was administered to 20 service technicians in the Klang Valley. The result indicates the service technicians are often involved in communication activities: introduction; describing services, processes and people; telephone communication; responding to complaints and; giving suggestions and providing advice that relates to pest control. The findings also reveal that the essential skills that pest control service technicians need for efficient job performance are listening and speaking skills; thus, any course to enhance English language proficiency among this group of service providers should centre on these two skills.